PENGARUH KOMPETENSI INTELEKTUAL, KOMPETENSI EMOSIONAL, DAN KOMPETENSI SOSIAL TERHADAP KINERJA GURU SMA SWASTA DI KOTA MALANG - Hallie Josias Sahertian; Veronica Jolanda Satriobudi (Universitas Trunojoyo Madura, 2016)
With the adoption of MEA in 2016, building an education is very important in creating good human resources that are superior and competitive. Indonesia need professional teachers. Teachers professionalsm will give impact in creating superior human resources that are ready to compete in MEA. However the result of National exam for high school in Malang 2016 showed that 19 students did not pass the exam and 11 of them are from private high school. The purpose of this research are to measure the impact of intellectual competence, emotional competence,and social competence on teacher performance of private high school in Malang. Hypothesis result stated intellectual competence,emotional competence, and social competence affect the teacher’s performances in positive result. This research proved that the most dominant factor was intellectual competence (X1). There are many ways to improve the teacher’s intellectual competence. Government can give scholarship to the teacher, as school can give training for the teacher for other private teacher can share their experiments and keep learning.